A sustainability assessment framework for bridges – a case study: Victoria and Champlain Bridges, Montreal. Issue 11 (1st November 2016) - Ali, Muhammad Shafqat; Aslam, Muhammad Sagheer; Mirza, M. Saeed
Abstract: This paper deals with the development of a framework for assessment of sustainability of bridges, including related technical, economic, environmental and social issues. Sustainable infrastructure assets require diligent conception and design of facilities (with diligent choice of materials and construction techniques), high quality construction, and operations, involving routine maintenance, with optimised life-cycle performance and costs, and minimum impact on the environment over a stipulated long service life and beyond. Partial details of design, construction, maintenance and rehabilitation/renovation of the four versions of the 3-km long Victoria Bridge (1859, 1898, 1958 and 1988) are summarised, along with the partial details of design, construction, severe deterioration and subsequent rehabilitation of the nearly 6-km long, 6-lane Champlain Bridge. Sustainability of both bridges was assessed by implementing the proposed sustainability framework developed in this research programme, along with the use of the analytical hierarchy process which involved evaluation of pairwise comparison of the various categories to assist with evaluation of the sustainability scores. These scores indicate that all four forms of Victoria Bridge (1859, 1898, 1958 and 1988) are partially sustainable, or sustainable, while the Champlain Bridge is unsustainable. This framework can be appropriately adapted for assessing the sustainability of other infrastructure assets.